I would say that they didnt because if you plug anythin in that equation it wont be a solution......i think thats what it meant
Answer:
6
Explanation:
According to secant-secant theorem,
(PB)(PA)=(PD)(PC)
(7)(12)=(PD)(14)
NOW
84/14 = PD
PD = 6
If you would like to find a factor of 6x^2y + 8x^2 - 30y - 40, you can calculate this using the following steps:
<span>6x^2y + 8x^2 - 30y - 40 = 2x^2 * (3y + 4) - 10 * (3y + 4) = (3y + 4) * (2x^2 - 10) = 2 * (3y + 4) * (x^2 - 5)
</span>
The correct result would be 3y + 4.